Comparison of two ELISA methods for detection of antibodies against Footand- Mouth Disease virus of cattle breeds in Turkey - INCE, Ö. B.; KALKAN, R.; ÇAKIR, S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The study was conducted using two ELISA methods - the liquid phase blocking ELISA (LPBE) and solid phase competition ELISA (SPCE) for the detection of foot-and-mouth disease virus (FMDV) serotype A- and O-specific antibodies of different cattle breeds in Turkey. These methods were compared in 426 cattle previously vaccinated with oil-adjuvanted bivalent vaccine as well as in sera from 40 cattle with no history of foot-and-mouth disease infection or vaccination. The results were found that SPCE had a better specificity (serotype A; 100% and serotype O; 97.50%) than LPBE (serotype A 95.00% and serotype O 92.50%). Sensitivity of SPCE had also better values (serotype A; 99.30% and serotype O; 98.59%) than LPBE (serotype A; 97.89% and serotype O; 96.48%). The results of the present study showed that the SPCE method is more reliable than LPBE.